2013
DOI: 10.1002/cbf.2956
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3‐induced intestinal calcium transport is impaired in β‐globin knockout thalassemic mice

Abstract: Besides being a common haematological disorder caused by a reduction in β-globin production, β-thalassemia has been reported to impair body calcium homeostasis, leading to massive bone loss and increased fracture risk. Here, we demonstrated that heterozygous β-globin knockout thalassemic mice had a lower rate of duodenal calcium absorption compared with the wild-type littermates, whereas the epithelial electrical parameters, including transepithelial resistance, were not affected, suggesting no change in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…†Values are the magnitudes of PD, and the apical side is negative with reference to the basolateral side. PMCA 1b , or nuclear vitamin D receptor (VDR) in thalassemic mice (5). Therefore, it might be the iron hyperabsorption that hindered duodenal calcium transport in BKO mice, which as shown here could be completely restored by 1,25(OH) 2 D 3 and hepcidin administration.…”
Section: Discussionmentioning
confidence: 62%
“…†Values are the magnitudes of PD, and the apical side is negative with reference to the basolateral side. PMCA 1b , or nuclear vitamin D receptor (VDR) in thalassemic mice (5). Therefore, it might be the iron hyperabsorption that hindered duodenal calcium transport in BKO mice, which as shown here could be completely restored by 1,25(OH) 2 D 3 and hepcidin administration.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, ␤-thalassemia was previously found to disrupt intestinal absorption of both calcium and vitamin D (1,32,39), thereby curtailing calcium supply for bone mineralization. Suppression of intestinal calcium absorption in thalassemic mice was very severe, with 40 -50% reduction in the duodenal calcium transport rate, which was also intractable to a standard 1,25(OH) 2 D 3 supplementation (1 g·kg Ϫ1 ·day Ϫ1 sc for 3 days), a regimen known to markedly stimulate calcium absorption in wild-type mice (5). A study in homozygous ␤-thalassemia patients also confirmed the presence of fecal calcium wasting (21).…”
Section: Discussionmentioning
confidence: 70%
“…Our recent preliminary study in sexually mature male hemizygous ␤ IVSII-654 thalassemic mice showed that ␤ IVSII-654 -induced thalassemia tended to be associated with low bone mineral density (BMD) and impaired bone microstructure (30). What caused this skeletal defect in thalassemic mice was not known, but it was suggested that impaired intestinal calcium absorption could have eventually led to increased osteoclast activity and excessive bone resorption (5,30). A body of evidence also strongly suggested the presence of age-and sex-dependent regulation of calcium and bone metabolism.…”
mentioning
confidence: 99%
“…Interestingly, the hemizygous ␤-globin knockout thalassemic (BKO) mice also exhibited a marked decrease in 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ]-dependent calcium absorption in the small intestine, which might, in turn, diminish matrix mineralization and bone formation (7). Moreover, the thalassemia-induced intestinal malabsorption of vitamin D and disturbances of calciotropic hormones, such as low serum levels of parathyroid hormone (PTH) and vitamin D, could further aggravate the impairment of bone metabolism (2,50,63).…”
mentioning
confidence: 99%
“…Two groups of data with normal distribution were compared by unpaired Figs. 3,7,and 8), whereas data with nonnormal distribution were compared by nonparametric Mann-Whitney test (i.e., Figs. 1,2,4,5,6,and 9).…”
mentioning
confidence: 99%